(untitled) (Al-Qamar, 2021)
The twentieth century is the period of awakening of consciousness and revival of Islam. Therefore, this is the period of revival and evolution of Islamic movements. After the imperialist domination of British imperialism in the subcontinent, like other spheres of life of the Muslim Ummah, there were changes in jurisprudential and legal thought. Maulana Maududi was one of the most influential Islamic thinkers of the twentieth century. His thoughts, ideas and writings have had a profound effect on the evolution of Islamic movements around the world, Thoughts changed. Maulana Maududi has a moderate view of jurisprudence .In this article presents an analytical study of Maulana Maududi’s concept of Jurisprudence.